2017
DOI: 10.1021/acssynbio.7b00295
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Gene Repression Using Novel Bifunctional Molecules to Harness Endogenous Histone Deacetylation Activity

Abstract: Epigenome editing is a powerful method for life science research and could give rise to new therapies for diseases initiated or maintained by epigenetic dysregulation, including several types of cancers and autoimmune disorders. In addition, much is still unknown about the mechanisms by which histone-modifying proteins work in concert to properly regulate gene expression. To investigate and manipulate complex epigenetic interactions in live cells, we have developed a small molecule platform for specifically in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
0
18
0
1
Order By: Relevance
“…We have previously demonstrated the ability of chemical epigenetic modifiers (CEMs) to modify chromatin and subsequently repress gene expression at engineered reporter loci 14 . In this study, we report CEM activating (CEMa) molecules that recruit endogenous gene activating machinery.…”
mentioning
confidence: 99%
“…We have previously demonstrated the ability of chemical epigenetic modifiers (CEMs) to modify chromatin and subsequently repress gene expression at engineered reporter loci 14 . In this study, we report CEM activating (CEMa) molecules that recruit endogenous gene activating machinery.…”
mentioning
confidence: 99%
“…To address these concerns, synthetic bifunctional ligands, termed chemical epigenetic modifiers (CEMs), were developed to target endogenous epigenome modifiers (Figure 2c). The first generation CEMs conjugate FK506 (a ligand binds FKBP12) to histone deacetylase (HDAC) inhibitors that recruits HDAC-containing corepressor complexes [92,93]. Using these CEMs in the CiA system with the GAL4DBD-FKBP12 fusion protein, endogenous HDAC3 can be targeted to the CiA:OCT4 locus leading to the reduction of H3K27ac and gene silencing in revisable and dose-dependent manners [92].…”
Section: Chemical Epigenetic Modifier (Cem)-based Editingmentioning
confidence: 99%
“…The first generation CEMs conjugate FK506 (a ligand binds FKBP12) to histone deacetylase (HDAC) inhibitors that recruits HDAC-containing corepressor complexes [92,93]. Using these CEMs in the CiA system with the GAL4DBD-FKBP12 fusion protein, endogenous HDAC3 can be targeted to the CiA:OCT4 locus leading to the reduction of H3K27ac and gene silencing in revisable and dose-dependent manners [92]. To expand the CEM strategy for broader applications, a second generation CEM platform was recently developed that incorporated the CRISPR/dCas9 system for DNA targeting [93].…”
Section: Chemical Epigenetic Modifier (Cem)-based Editingmentioning
confidence: 99%
“…This is accomplished by (1) redirecting the HDAC to the locus, releasing the enzyme, and increasing the density of un-inhibited HDACs in the area and (2) maintaining HDAC inhibition at the locus, but recruiting repressive complexes that bind to the inhibited HDACs, or (3) a combination of both. In a previous study, we showed that the CEMs were able to successfully repress the GFP reporter in a dose-and time-dependent manner, as well as in a manner that was rapidly reversible (i.e., within 24 hours) 12 . We characterized the ability of the CEM technology presented here to control gene expression using fluorescence microscopy, flow cytometry, and the ability to control the chromatin environment using ChIP-qPCR 6 .…”
Section: Introductionmentioning
confidence: 95%
“…The linker length between FK506 and the recruiter moiety will influence the permeability of the CEMs, as well as the position of the recruited protein. When comparing two CEMs that differed only in linker length, the CEM with the shorter linker was more effective 12 . While it has not been tested directly here, the higher effectiveness is a result of greater cell permeability.…”
mentioning
confidence: 99%